The impact of death and caring for the dying and their families on surgeons - an AI assisted systematic scoping review - Jun Rong Tan; Yun Ting Ong; Victoria Jia En Fam; Annushkha Sinnathamby; Nila Ravindran; Yaoyi Ng; Lalit Kumar Radha Krishna (BMC Surgery)
Abstract Context Surgeons are taking central roles in caring for patients leaving them prone to the emotional turmoil and grief of patients and families and the moral, psychological and existential distress of members of the interprofessional team and trainees. This has implications on patient safety and surgeon welfare. Objectives A systematic scoping review was carried out to address the primary research question “what is known of the effects of caring for the dying and the impact of patient’s death on surgeons?”. It is hoped that the insights gained will better guide support and assessment of surgeons in their evolving roles. Methods Guided by the Systematic Evidence-based Approach (SEBA), we conducted a systematic scoping review (SSR). This review included articles published between 1st January 2000 and 2nd September 2024 on Pubmed, Embase, Scopus, Google Scholar, ERIC databases. To enhance trustworthiness and enhance the comprehensiveness of our review the articles identified were also evaluated using ChatGPT 4o and Notebook LM. The findings of these assistive processes were compared with the independent thematic and content analysis carried out by the two research teams. Results In total, 4966 titles and abstracts were identified, 174 full-text articles were reviewed, and 26 full-text articles analysed. With the findings of the assistive analysis by the AI tools echoing the findings of the research teams- two key domains were identified: (1) the impact on personhood, (2) predisposing factors. Conclusion This AI assisted SSR in SEBA confirms that surgeons do suffer from the cumulative effects of caring for dying patients and their families and from the death of the patient and supporting the family and members of the interprofessional team and trainees. Without timely and personalized support surgeons are prone to depression, burnout, and substance abuse, and compromises to patient and family experiences, outcomes, safety and satisfaction. The need for effective longitudinal and personalized assessment tools is clear.